Scope of Big Data and Its Applications - Devendra Singh Kushwaha, Shaibya Singh, Dr. Vikash K Singh, (International Journal of Scientific Research and Management (IJSRM), 2015)
Now a day’s everyone has been speaking about Big Data for some time, but there is a lot of rumor and tire kicking by many in the industry. We wanted to evaluate how people are viewing Big Data today, how important it is, how to deal with it, what returns can be had from it… Big data is the term for data sets so large and complicated that it becomes difficult to process using traditional data management tools or processing applications. It is already true that Big Data has drawn huge attention from researchers in information sciences, policy and decision makers in governments and enterprises. As the speed of information growth exceeds, excessive data is making great troubles to human beings. However, there are so much potential and highly useful values hidden in the huge volume of data. A large number of fields and sectors, ranging from economic and business activities to public administration, from national security to scientific researches in many areas, involve with Big Data problems. On the one hand, Big Data is extremely valuable to produce productivity in businesses and evolutionary breakthroughs in scientific disciplines, which give us a lot of opportunities to make great progresses in many fields. There is no doubt that the future competitions in business productivity and technologies will surely converge into the Big Data explorations. On the other hand, Big Data also arises with many challenges, such as difficulties in data capture, data storage, and data analysis and data visualization. This paper is aimed to demonstrate a close-up view about Big Data, including Big Data applications, Big Data opportunities and challenges, as well as the state-of-the-art techniques and technologies we currently adopt to deal with the Big Data problems.